2022
DOI: 10.3390/land12010070
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Net Environmental and Economic Impacts of Urban Forests: An Online Decision Support Tool

Abstract: Nature-based solutions (NBS) are becoming popular in urban planning and policy making as cost-effective solutions capable of delivering multiple ecosystem services and addressing several societal challenges. So far, however, the cost-effectiveness of urban NBS projects has not been consistently quantified by built environment professionals, who lack user-friendly tools to account for the environmental costs and benefits of NBS. This paper presents a prototype online decision support tool (NBenefit$®) that calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Figure 5 graphically illustrates the relationships between ES supply and ES demand in terms of potential indicators that can be retrieved from both LCA and ESA literature. The use case in the figure is retrieved and adapted from Babí Almenar et al [92] and includes the typical life cycle phases and ES supply/demand (impact) flows associated with the implementation of green infrastructure in cities (urban forests in this case). The notion of time and space is also included in the source model, but not visualized in the example of Figure 5 for the sake of simplicity.…”
Section: Limitations and Identification Of Natural Capital Dependenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 graphically illustrates the relationships between ES supply and ES demand in terms of potential indicators that can be retrieved from both LCA and ESA literature. The use case in the figure is retrieved and adapted from Babí Almenar et al [92] and includes the typical life cycle phases and ES supply/demand (impact) flows associated with the implementation of green infrastructure in cities (urban forests in this case). The notion of time and space is also included in the source model, but not visualized in the example of Figure 5 for the sake of simplicity.…”
Section: Limitations and Identification Of Natural Capital Dependenciesmentioning
confidence: 99%
“…Figure 5. Relationship between ES demand and supply indicators in the case of a restoration/renaturation project implemented for residual environmental footprint offsetting purposes; source: core framework and image adapted from Babí Almenar et al[92].…”
mentioning
confidence: 99%
“…Among all the studies, only 10 (36%) reported decision support processes that existed in digital formats. A range of methods were employed in the development of these decision frameworks, models, and tools, including stakeholder engagement [45][46][47][48], literature reviews [49][50][51][52], primary data collection [43,44,53], and secondary data analysis [54][55][56][57][58][59][60][61]. Some studies combined methods, such as utilizing both literature reviews and primary data [62,63], both literature reviews and secondary data [64][65][66], both stakeholder engagement and secondary data [67], and both primary and secondary data [68].…”
Section: Description Of Tools and Frameworkmentioning
confidence: 99%
“…Table 1 presents a summary of the synthesized results and scores for the reviewed frameworks, models, and tools based on how well they incorporate health, environmental, and economic benefits of trees and greenspace. Among the 28 studies analyzed, several patterns emerged: 11 studies [43][44][45][46][48][49][50]59,65,66,69] demonstrated the incorporation of at least one element from each of health, environmental, and economic dimensions; 5 studies integrated benefits from both the environmental and economic dimensions [47,51,[56][57][58]; and 5 studies [51,56,60,64,67,68] combined health and environmental dimensions simultaneously.…”
Section: Integration Of Greenspace Benefits Into Decision-making Proc...mentioning
confidence: 99%